Program Aktualisasi Nilai-Nilai Pancasila dengan Mengimplementasikan Pancasila Sila Ke-1 - Pipih Nurlaela; Reizika Mahadewi Novia; Rifan Aziel Zulfikar; Risqi Wijaya; Salsabila Nur Muhtar; Sinta Nurlaela; Syifa Nurrohmatillah; Vira Nurmala; Bobang Noorisnan Pelita; Dian Herdiana (AMMA : Jurnal Pengabdian Masyarakat, 2022)
One example of actualizing Pancasila values ​​is by implementing the first Pancasila precepts, namely in this activity through teaching and practicing short letters in the family and community environment. This study aims to explore and examine information about the application of Pancasila values ​​through teaching programs and practicing letters in the family and community environment which is carried out in each respective area. The results of this study are (1) the introduction of the values ​​of the first precepts (2) Provide positive reinforcement and it is hoped that children can hold fast to the Qur'an and can practice the contents of the short letters (3) Implementation of this building the foundation of the nation's generation of children can be found in the first place with the devotion to God Almighty as Pancasila the first precepts (4) Cultivating the values ​​of the first precepts in the family and community environment (5) The solution in overcoming various problems of implementing Pancasila Pancasila in the family and community environment is the existence of support from parents, community, and government in every implementation activity